Концептуальні засади поведінкових наук як теорії людських ресурсів - Бажан, Л.І.; Яблоков, І.В. (Економіко-математичне моделювання соціально-економічних систем, 2016)
Relationship between behavioral science, theory of human resources and personnel is investigated. Conceptual approaches to human resource management in conjunction with their behavior are elaborated. Process of transformation from personnel management towards human resource management under conditions of rising competition is considered.